2015
DOI: 10.1016/j.kjms.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Posterior pole asymmetry analysis and retinal thickness measurements in young relatives of glaucoma patients

Abstract: The presence of a family history of glaucoma is a known risk factor for primary open-angle glaucoma (POAG) in middle-aged and older individuals. In this study, our aim was to demonstrate possible early glaucomatous alterations in young first- and second-degree relatives of POAG patients by spectral-domain optical coherence tomography. A total of 104 participants (52 relatives of POAG patients and 52 healthy individuals) were recruited in this cross-sectional study. All the participants were between 17 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
1
18
3
Order By: Relevance
“…The cited authors concluded that young relatives (aged 17 to 45 years) of POAG patients did not exhibit characteristic glaucomatous damage when compared to controls. The differences between our data and those of Pekel and colleagues may be associated with a difference in the age of the study groups. The mean age of our subjects was 55 years, which is higher than that of the subjects considered by Pekel and colleagues .…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…The cited authors concluded that young relatives (aged 17 to 45 years) of POAG patients did not exhibit characteristic glaucomatous damage when compared to controls. The differences between our data and those of Pekel and colleagues may be associated with a difference in the age of the study groups. The mean age of our subjects was 55 years, which is higher than that of the subjects considered by Pekel and colleagues .…”
Section: Discussioncontrasting
confidence: 97%
“…The differences between our data and those of Pekel and colleagues may be associated with a difference in the age of the study groups. The mean age of our subjects was 55 years, which is higher than that of the subjects considered by Pekel and colleagues . Retinal nerve fibre layer thinning is associated with aging; several authors have reported inverse correlations between age and retinal nerve fibre layer thickness.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…
We thank Pekel et al 1 for their interest in our work 2 and for the opportunity to discuss the findings of our study. They mentioned in their study that the mean retinal arteriolar caliber did not statistically differ between young relatives of patients with open-angle glaucoma (OAG) and age-matched healthy controls; however, we would like to point out that not all relatives of patients with OAG progress to glaucoma.
…”
mentioning
confidence: 85%